Erratum: Information and Communication Technology Use Capacity Within Extension Networks: Development and Preliminary Validation of an Empirical Scale - JIAEE Editors (Journal of International Agricultural and Extension Education, 2024)
Correction: The DOI of the article "Lamm, K. W., Davis, K., Sanders, C. E., & Powell, A. (2021). Information and Communication Technology Use Capacity Within Extension Networks: Development and Preliminary Validation of an Empirical Scale. Journal of International Agricultural and Extension Education, 28(4)” was incorrect as published. The correct DOI is: 10.5191/jiaee.2021.28408